Normative profiles of sports performance - O'Donoghue, P. (International Journal of Performance Analysis in Sport, 2005)
Performance indicators in sport are not stable properties of individual competitors or teams and a single athlete's (or team's) performance will vary from match to match. For this reason, Hughes, Evans and Wells (2001) developed a technique for determining "normative profiles in performance analysis". This paper proposes an alternative technique that represents not only the typical performance of a team or individual but also the spread of performances. The technique also relates the set of performance indicators for a team or individual to normative data for a relevant population of teams or individuals. This provides a useful means of interpreting sports performance data. Grand Slam singles tennis is used as an example of the application of the proposed technique for determining a normative profile of a team's or individual's performance. It is recognised that the mean value for each performance indicator within the typical performance is critically important information that should be supported by rather than replaced by percentile bandings.